Is The TEFL Teacher a Hostage in ESP? An Overview of the Recent Status and Problems of the TEFL Teacher in ESP - Khuwaileh, Abdullah Aied (The ESPecialist, 2012)
The emergence of ESP (English for Specific Purposes) early in the 1960s was an important development that has made the task and function of ELT, in the field of ESP, more complex and sometimes insecure. The purpose of this article is to shed some light on the status and problems of the TEFL teacher in ESP, the problems which have made him a hostage to many variables and difficult conditions, rather than the king of his classroom. While the title of this article may imply negative connotations, newcomers (new ESP teachers) need not be horrified about the conditions that surround their (future) profession. We believe that tackling the problems and pitfalls that ESP teachers encounter can help to improve ESP teaching and learning. To achieve the objective of the article, we will deal with various external and internal problems that face the ESP teacher. The article will then end up with a number of conclusions and recommendations about the improvement of the ESP teacher’s conditions. These recommendations may help to bring about the hope and job satisfaction for TEFL teachers in the ESP camp.